Selection of Simple Prose Texts. - Babaee, Ruzbeh (Cambridge Scholars Publishing, 2017)
This book introduces a number of different types of writing taken from various periods in history and from well-known authors. It serves as an introduction to English-language prose. The texts compiled here are relevant to current social issues and problems, and, as such, will arouse the curiosity and interest of the reader.